The Challenging of Rehabilitation Medicine in Covid-19 - Retno Setianing (Indonesian Journal of Physical Medicine & Rehabilitation, 2020)
The WHO declared a pandemic due to the serious health risk posed by Coronavirus disease (COVID-19). The number of infected cases is on the rise globally with escalating human, economic and societal costs. COVID-19 survivors may suffer a range of clinical, functional and psychological impairments, resulting in disabilities. It was confirmed to have spread to Indonesia on 2 March 2020. Many are amenable to rehabilitation intervention because the current focus of COVID-19 management is on public health measures and acute management. As patients transfer to sub-acute care or discharged to the community, rehabilitation services need to have a number of organizational and operational models in place to provide safe effective care for patients and health professionals. The post-acute management and rehabilitation of the current COVID-19 survivors will be the focus in the coming months, given the range of functional, psychological and clinical impairments reported in many patients. Early rehabilitation intervention in the critical care environments after comprehensive assessment by an interdisciplinary team is safe and essential. Therefore, it is necessary to knowledge and prepare a health service standard to optimize quality of life in disaster victims through holistic and comprehensive approach. New scientific information is emerging and clinical care is driven by rapidly accumulating knowledge.